Factors associated with compliance with NBCAL in establishments in Belém/PA (Research, Society and Development, 2022)
Objective: To analyze the association between the training of professionals and the presence of representatives of the industry/companies of breastmilk substitutes with the occurrence of infractions in commerce in Belém/Pa. Method: Cross-sectional study that makes up a multi-center epidemiological survey, which aimed to assess compliance with NBCAL in all regions of the country. The population consisted of managers or persons responsible for commercial establishments found in the environments at the time of the visit. Data analysis was performed using absolute and relative frequencies and logistic regression. Results: Establishments that are part of the network (RP = 4.56; 95% CI = 1.94-10.73), classified as large / hyper (RP = 1.53; IC95 = 1.07-2.17), which receive visits from industry representatives / companies of LM substitutes and Childcare products (PR = 2.86; CI9% = 1.43- 5.72), where managers or guardians were male (CI95% = 1.06- 5.06) and where the disposition of products on the shelves was defined by the matrix (CI95% = 1.64 - 6.34), showed a statistically significant association with infractions. Conclusions: Most professionals do not have training on NBCAL and breastfeeding and infant feeding; the presence of representatives of the product industry covered by NBCAL was related to the occurrence of infractions in the establishments.